Efficient Control Design for the Single Phase Grid Tie Inverter Using Wave Shape Coping Pulse Width Modulation Technique - Taj, A. B.; Ahmad, M. (The Nucleus, 2020)
The aim of this paper is to achieve the efficient control design for a single phase grid tie inverter (GTI) using PROTEUS Professional software and its practical implementation. Unique thought is given to the way that, dissimilar to customary standalone inverters, GTI are required to satisfy the demands associated with each phase of the grid. Photovoltaic module and single-phase GTI both are tied together using an inverter. In this paper we have got the reference voltage from the main grid using operational amplifier, Wave Shape Coping Pulse Width Modulation (WSPWM) technique is applied with PIC16F877A microcontroller and IR2110 gate driver which drive the MOSFET IRF840 after appropriate filtering and control the power supply to the grid with appropriate isolation. The functional testing of the single phase GTI has been performed successfully when DC-AC conversion occurs. Beside the ability of GTI, its frequency and output voltage had consistent fluctuations due to the change in frequency and grid voltage. Another feature of the GTI is that if the power from electrical grid is zero, the inverter will stop the process of inversion and just supply zero voltage output at that time. Accordingly, quick shut down of DC-AC process of inversion happens if there arises a sudden dark out period. It is worth mentioning that the designed GTI cannot be operated without reference voltage of the grid and connected directly to PV solar panels.